ANALISA KEBUTUHAN KAPAL FERRY TERNATE – TIDORE - Irnawaty, Irnawaty; Saputra, Muhammad Taufiq Yuda (Fakultas Teknik Universitas Khairun, 2024)
Ferry transport is a form of transportation system that can connect regions in Indonesia to support the economy and development in areas separated by water. One of the crossings currently operating is the Ternate–Tidore crossing. The Ternate-Tidore crossing is an inter-city crossing that connects the cities of Ternate and Tidore. This research aims to find out how much cargo growth (passengers, R2, R4/6, and goods) will increase on the Ternate-Tidore crossing in the future, namely in the next 10 years, namely 2023 - 2032 and to find out how much the ferry crossing needs. Ternate - Tidore crossing in 2032. The method used in this research is a quantitative research method, because the data taken is quantitative data, in data management the methods used are the Least Square Method and the Geometric Method. Based on research results, the average load growth over the next 10 years, namely from 2023 - 2032, is 4% for passengers, 5% for R-2 vehicles and 5% for R-4/6 vehicles and 6% for goods and Load Factor in 2032 has reached 1.3%, which means that the level of demand for ferry transportation has exceeded the available capacity, which is in accordance with the requirements issued by the Ministry of Transportation through the Directorate General of ASDP that the Load Factor for public transportation is a maximum of 1.1%. This condition shows that the loading capacity of Ferry ships or (load factor) in 2013 cannot be maintained until 2032. Therefore, the need for Ferry ships to be operated for the next 10 years, namely 2023 - 2032, is 6 ships with a trip of 13 trips/passage.Ferry transport is a form of transportation system that can connect regions in Indonesia to support the economy and development in areas separated by water. One of the crossings currently operating is the Ternate–Tidore crossing. The Ternate-Tidore crossing is an inter-city crossing that connects the cities of Ternate and Tidore. This research aims to find out how much cargo growth (passengers, R2, R4/6, and goods) will increase on the Ternate-Tidore crossing in the future, namely in the next 10 years, namely 2023 - 2032 and to find out how much the ferry crossing needs. Ternate - Tidore crossing in 2032. The method used in this research is a quantitative research method, because the data taken is quantitative data, in data management the methods used are the Least Square Method and the Geometric Method. Based on research results, the average load growth over the next 10 years, namely from 2023 - 2032, is 4% for passengers, 5% for R-2 vehicles and 5% for R-4/6 vehicles and 6% for goods and Load Factor in 2032 has reached 1.3%, which means that the level of demand for ferry transportation has exceeded the available capacity, which is in accordance with the requirements issued by the Ministry of Transportation through the Directorate General of ASDP that the Load Factor for public transportation is a maximum of 1.1%. This condition shows that the loading capacity of Ferry ships or (load factor) in 2013 cannot be maintained until 2032. Therefore, the need for Ferry ships to be operated for the next 10 years, namely 2023 - 2032, is 6 ships with a trip of 13 trips/passage.